Relaksasi Otot Progresif dalam Manajemen Nyeri Pembedahan Ortopedi - Hendayani, Nurul; Masfuri, Masfuri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This writing aims to determine the effect of progressive muscle relaxation as a non-pharmacological therapy that can be used as a complementary or additional therapy in pain management in patients after orthopedic surgery. The method used was a systematic search for articles through the PubMed, Science Direct, Proquest, and Francis Taylor databases and published from 2013 to 2023 using the keywords